Pelatihan Self-Disclosure melalui Guided Group Journaling - Sulaiman, Dwi Rezky Anandari; Alifya; Asmaul; Ayu (Jurusan Pendidikan Teknik Elektro, 2025)
Self-disclosure is a critical interpersonal skill in fostering effective communication, especially for university students who serve as mentors for incoming freshmen. The ability to disclose personal thoughts, feelings, and experiences enables mentors to build empathetic and supportive relationships with their mentees, creating a positive and trusting mentoring environment. However, not all students possess the confidence or ability to express themselves openly. This community service program aimed to develop students' self-disclosure skills through a guided group journaling approach—a structured reflective writing technique conducted in groups. The implementation methods included training sessions, guided journaling, group discussions, and collective reflection. The results indicated an increased willingness among participants to share personal experiences, along with heightened self-awareness and empathy toward others. Moreover, participants reported that journaling helped them understand their own emotions better and feel more prepared for their mentoring roles. This program demonstrates that guided group journaling is an effective strategy for equipping students with essential interpersonal skills, particularly within the context of peer mentoring in higher education.